Creating a Social Learning Environment for and by Older Adults in the Use and Adoption of Smartphone Technology to Age in Place - Haan, Marjolein den; Brankaert, Rens; Kenning, Gail; Lu, Yuan (Frontiers in Public Health, 2021)
Older adults may benefit from modern technologies supporting aging in place, but they can struggle with accepting and adopting novel technologies into their daily lives. Many studies have investigated the potential of mobile health interventions. We are interested in contributing to this by creating a social learning environment close to people’s homes for and by older adults in the use and adoption of smartphone technology to promote active lifestyles. We followed a community group learning to use a novel smartphone interface designed for older adults, including fall prevention and detection, activity tracking, and an interface that can evolve in line with the users’ learning curve. They gathered together in a community house, on walking distance from their homes. We explored the determining factors that prompted and facilitated older adults to start and continue using a smartphone technology platform. By this, we learn how smartphone technology can be introduced and designed for sustainable use. We found that social facilitation, by super-users and peers in combination with adaptive technology and recall tools, supports smartphone learning by older adults. To conclude, we provide hands-on suggestions to set up a social learning environment for older adults to learn new technologies and insights into what motivates them to start and continue using this technology, supporting aging in place.